1997
DOI: 10.2337/diab.46.3.456
|View full text |Cite
|
Sign up to set email alerts
|

Visceral Fat and Race-Dependent Health Risks in Obese Nondiabetic Premenopausal Women

Abstract: Our previous finding that a waist-to-hip ratio (WHR) >0.85 was not associated with similar health risks in black, compared with white, obese premenopausal non-diabetic women of similar fatness is attributed to either 1) a different relationship between WHR and visceral adiposity or 2) differences in the relationship between visceral adiposity and the metabolic abnormalities of obesity. We measured visceral (VAT) and subcutaneous adipose tissue (SCAT) areas at midwaist in 25 black and 25 white obese nondiabetic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
72
1
1

Year Published

1998
1998
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 203 publications
(81 citation statements)
references
References 0 publications
7
72
1
1
Order By: Relevance
“…Black persons have generally less visceral fat compared with white persons, whereas the subcutaneous fat (either abdominal or at the thigh) is higher, for any level of total body fat. Black people had a better lipid profile in our data, which has also been found previously [36,37]. It has been shown that in both sexes black persons have higher LPL activity and lower HL activity compared with white persons [36], which may explain these differences in lipid profile and fat distribution.…”
Section: Discussionsupporting
confidence: 77%
“…Black persons have generally less visceral fat compared with white persons, whereas the subcutaneous fat (either abdominal or at the thigh) is higher, for any level of total body fat. Black people had a better lipid profile in our data, which has also been found previously [36,37]. It has been shown that in both sexes black persons have higher LPL activity and lower HL activity compared with white persons [36], which may explain these differences in lipid profile and fat distribution.…”
Section: Discussionsupporting
confidence: 77%
“…However, this concept or hypothesis is more applicable and relevant in several non-black populations, but remains controversial in blacks. For identical BMI, recent studies showed that black adults and youth residing in diverse geographic locations have lower visceral adiposity despite increased insulin resistance when compared with whites [44][45][46][47].…”
Section: Paradox Of Insulin Resistance Body Composition and Mets Inmentioning
confidence: 98%
“…In blacks, WC is the most common component of MetS [11, 14-16••, 18]. WC serves as a surrogate for intraabdominal visceral adipose tissue (VAT) and an important determinant of insulin resistance and its concomitants for CVD in non-black populations [44][45][46][47]. However, this concept or hypothesis is more applicable and relevant in several non-black populations, but remains controversial in blacks.…”
Section: Paradox Of Insulin Resistance Body Composition and Mets Inmentioning
confidence: 98%
“…In addition to greater degrees of overall obesity, women with PCOS may be more likely to exhibit an abdominal and/or visceral pattern of fat distribution [10]. Because these depots are associated with a more adverse metabolic profile, including greater degrees of insulin resistance and glucose intolerance [11], the distribution of fat to abdominal/visceral sites has been offered as one explanation for the metabolic abnormalities observed in PCOS [10]. Nevertheless, there are many women with PCOS who are not overtly obese, yet are insulin resistant.…”
Section: Obesity and Abdominal Fat Distribution In Pcosmentioning
confidence: 98%